Recognition Before Authorization: Reconstructing FPIC for the Use of Ulayat Land of Customary Law Communities in South Papua - Muslim Lobubun (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Constitutional recognition of customary law communities does not, by itself, guarantee the protection of ulayat land when the state is preparing to issue administrative decisions that enable third parties to use such territories. This issue is particularly significant in Papua because the Special Autonomy regime requires the provision of ulayat land to be conducted through deliberation aimed at reaching agreement with the relevant customary law community. This study examines the legal position of recognition of customary law communities and Free, Prior and Informed Consent (FPIC) in decision-making concerning the use of ulayat land and formulates a legal framework that places the protection of ulayat rights before authorization is granted. This study employs normative legal research, using statutory, conceptual, and case approaches. The findings demonstrate that land administration and registration contribute to legal certainty for ulayat rights but cannot be treated as the sole basis for the existence of rights that positive law also links to the continuing factual existence of the community and its ulayat relationship with the land. The study proposes a recognition-before-authorization framework based on the principle of protective sequencing, comprising preliminary examination of indications of ulayat rights, temporary administrative safeguards, participatory inventory and mapping, strengthened recognition, substantive consent, and authorization only after land status and community consent have been resolved. This framework seeks to prevent delays in the administrative recognition of customary law communities from allowing third-party legal interests to be established ahead of ulayat rights over Indigenous territories.